Legal Protection of Wives from Domestic Violence Perspectives of Islamic Law and Positive Law - Mutiah, Mutiah; Satrianingsih, Andi; Anshar, Anshar; Hamzah, Nur Asia; Ilmah, Nurul (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
His study uses qualitative methods that aim to: 1). know how the concept of legal protection for wives from domestic violence from Islamic legal perspectives 2). Knowing the concept of legal protection for wives from domestic violence from a positive legal perspective. In answering these problems, researchers use the type of library research (library reseach), which is research conducted using literature (literature), both in the form of books, notes, and the results of previous researchers' reports. Or by studying the hadiths and verses of the Qur'an related to the problem in this study so that conclusions can be drawn.Based on the results of research and discussion, the author concludes that from several forms of domestic violence against wives and punishments applied according to Islamic Law, legal protection for women or wives who are victims of domestic violence is the husband's agreement with his wife during the marriage contract and the wife's right to the husband to ask for divorce (khuluk). The legal protection of wives from domestic violence from a positive legal perspective is in Law Number 23 of 2004 concerning the elimination of domestic violence article 10 by providing protection from the family, police, prosecutors, advocates, social institutions, or other parties both temporarily and based on the government. So the author concludes that committing violence against wives in Islamic law and positive law is not permissible whether the victim is the wife or husband, because in Islam it always teaches gentle behavior and affection between others and domestic violence is an act that is not justified in Islam. Penelitian ini menggunakan metode kualitatif yang bertujuan untuk: 1). mengetahui bagaimana konsep perlindungan hukum terhadap istri dari tindak KDRT perspektif hukum Islam 2). mengetahui konsep perlindungan hukum terhadap istri dari tindak KDRT perspektif hukum positif. Dalam menjawab permasalahan tersebut, peneliti menggunakan jenis penelitian kepustakaan (library reseach) yakni penelitian yang dilakukan dengan menggunakan leteratur (kepustakaan), baik berupa buku, catatan, maupun hasil laporan peneliti terdahulu. Atau dengan mengkaji hadits-hadits dan ayat-ayat Al-Qur’an yang berkaitan dengan permasalah dalam penelitian ini sehingga bisa diambil kesimpulan. Berdasarkan hasil penelitian dan pembahasan penulis mengambil kesimpulan bahwa dari beberapa bentuk-bentuk KDRT terhadap istri beserta hukuman yang diterapkan menurut Hukum Islam maka perlindungan hukum bagi wanita atau istri yang menjadi korban KDRT yaitu perjanjian suami atas istri ketika akad nikah dan hak istri atas suami untuk meminta cerai (khuluk). Adapun perlindungan hukum terhadap istri dari tindak KDRT perspektif hukum positif yaitu dalam Undang-undang Nomor 23 Tahun 2004 tentang penghapusan kekerasan dalam rumah tangga pasal 10 dengan memberikan perlindungan dari pihak keluarga, kepolisian, kejaksaan, advokat, lembaga sosial, atau pihak lainnya baik sementara maupun berdasarkan pemerintah. Jadi penulis mengambil kesimpulan bahwa melakukan kekerasan terhadap istri dalam hukum Islam dan hukum positif tidak dibolehkan baik itu korbannya istri ataupun suami, karena dalam Islam selalu mengajarkan berprilaku lembut dan kasih sayang antar sesama dan KDRT merupakan tindakan yang tidak dibenarkan dalam Islam.